Co-validação de diplomas de curso superior, por refugiados, no Brasil - Dornelles, Cassio Francisco Lutz (2022)
This work aims to address the problem involving the protection of people in refugee conditions, with integration in the host country being part of the migration cycle. Education is one of the doors for the restart and effective integration of these people. Therefore, it is worth asking how the implementation of a mechanism for the covalidation of university degrees, under the seal of UNESCO, would allow higher-level professionals from politically unstable territories, affected by armed conflicts (internal or external), to access the world of work in other national states quickly and effectively? The search for an answer indicates the general objective of the study: to propose a mechanism for the co-validation of university degrees, under the seal of UNESCO, which allows higher-level professionals from politically unstable territories, affected by armed conflicts (internal or external), access the world of work in other national states. In order to achieve the specific objectives, this study will be based on a bibliographical and documental research. As for the procedure, the historical method was used and the method of approach adopted for the present study is the deductive one. To achieve the objective, the work was organized, so that the first chapter covers international relations in the globalized world of work. The second begins with a study on diplomacy as an instrument for mediating international relations. The third chapter addresses UNESCO and university systems. The fourth chapter brings the diplomacy. And the last chapter brings a proposal for the co-validation of titles that confer an academic degree.